Standarisasi Resep Tanak Dadiah Di Kenagarian Pakan Sinayan Kecematan Banuhampu Kabupaten Agam - Rani Kurnia Putri; Anni Faridah; Wiwik Gusnita (Journal of Home Economics and Tourism, 2018)
This study aims to find a standard recipe tanak dadiah, and the quality of the tanak dadiah. This research is a qualitative and quantitative research using mixed methods (Mixed Method). This research was conducted in Kenagarian Pakan Sinayan Kecamatan Banuhampu Kabupaten Agam from the date of Januari 17, 2016 until August1, 2016. The data source is two fold: a source of qualitative data obtained from the expert community, the source of quantitative data obtained from five expert panelists made tanak dadiah in Nagari Pakan Sinayan. Quantitative data techniq is a questionnaire format organoleptic, Qualitative data analysis techniq using three grooves of activitie are reduction data, display data and verification. Analisis data quantitatif with formula (Mx = Ʃ x / N). Based on the quantitative results of organoleptic standardization recipe tanak dadiah which has been converted followed by organoleptic tests found the quality of the tanak dadiah include: shape (neat round), color (yellow), aroma (egg) and aroma (onion and garlic), texture (soft), taste (dadiah, egg, and tasteful).Keyword : Standard Recipe Tanak Dadiah, Quality